Low-Dose ACTH Therapy for Infantile Spasms - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The lowest effective ACTH dose, with fewest adverse effects, for the treatment of West syndrome (WS) was determined in a comparative, randomly assigned, controlled study involving 25 patients with cryptogenic (CWS, n=9) or symptomatic (SWS, n=16) WS, at the Department of Pediatrics, Tokyo Women's Medical University, Tokyo, Japan.